Efficacy of at home monitoring of foot temperature for risk reduction of diabetes‐related foot ulcer: A meta‐analysis. Issue 6 (8th June 2022) - Golledge, Jonathan; Fernando, Malindu E; Alahakoon, Chanika; Lazzarini, Peter A.; aan de Stegge, Wouter B.; van Netten, Jaap J.; Bus, Sicco A.
Abstract: Aims: To perform an updated systematic review of randomised controlled trials examining the efficacy of at‐home foot temperature monitoring in reducing the risk of a diabetes‐related foot ulcer (DFU). Methods: Systematic review performed according to Preferred Reporting Items for Systematic reviews and Meta‐Analyses guidelines. Risk‐of‐bias was assessed using version 2 of the Cochrane risk‐of‐bias tool. Meta‐analyses were performed using random effect models. Leave‐one‐out sensitivity analyses and a sub‐analysis excluding trials considered at high risk‐of‐bias assessed the consistency of the findings. The certainty of the evidence was assessed with GRADE. Results: Five randomised controlled trials involving 772 participants meeting the International Working Group on the Diabetic Foot (IWGDF) risk category 2 or 3 were included. All trials reported instructing participants to measure skin temperature at‐home at six or more sites on each foot using a hand‐held infra‐red thermometer at least daily and reduce ambulatory activity in response to hotspots (temperature differences >2.2°C on two consecutive days between similar locations in both feet). One, one, and three trials were considered at low, moderate and high risk‐of‐bias, respectively. Participants allocated to at‐home foot temperature monitoring had a reduced risk of developing a DFU (relative risk 0.51, 95% CI 0.31–0.84) compared to controls. Sensitivity and sub‐analyses suggested that the significance of this finding was consistent. The GRADE assessment suggested a low degree of certainty in the finding. Conclusions: At‐home daily foot temperature monitoring and reduction of ambulatory activity in response to hotspots reduce the risk of a DFU in moderate or high risk people with a low level of certainty.